A review analysis of the poaching and illegal trade of tortoises and freshwater turtles (TFTs) in Pakistan - safi, Amtyaz; Usman Ali Hashmi, Muhammad; ud Din Yousufzai , Sultan; Karl , Hans-Volker (SPC Journal of Environmental Sciences, 2024)
Despite legal protection, illegal trade in turtles and freshwater turtles continues in Pakistan, with many trade species destined for foreign markets. Pakistan's tortoises and hard-shelled turtles are mainly used in the pet trade, while its soft-shelled turtles are used in the meat trade. Given different economic conditions, the economic conditions of different groups of turtles and freshwater turtles will be different and therefore require different interventions. However, a systematic review of the illegal trade in turtles and freshwater turtles that considers the differences between these markets is not currently available. This study uses media seizure data to examine tortoises/hard-shell turtles (in demand in the pet trade) and softshell turtle (meat trade) supply chains. The tortoise/hard-shell turtle network has a larger geographic area and more global trade connections than the soft-shell turtle network. Our current clinical research provides insight into the similarities and differences in illegal activity for different groups of turtles and freshwater turtles, addressing the needs of different markets and demonstrating the need for effective strategies to tackle illegal trade in each group.